Second Language Development (SLD): What Factors Might Affect Students’ English Learning During Covid19 Pandemic - Ramli Ramli; Winarno Winarno; Fitriawati Fitriawati (Makassar State University, 2022)
Abstract. This study aimed to investigate factors affecting the students’ L2 language development. This issue was raised because second language acquisition is one of the most impressive and fascinating aspects of human communication skills. This study was also intended to help students effectively learn and understand the language. This was a descriptive quantitative study. The samples were 158 preservice students in the English Education Department, Universitas Borneo Tarakan. This data was collected using an online questionnaire through google form to indicate the students’ responses on how English as a second language is acquired by the learning experience and was analyzed using factorial analysis (principle componential analysis). This research found that second language development is affected by linguistic factors like vocabulary enrichment, the structure of the native language, and the ability to pronounce words. Besides, non-linguistic factors like cognitive styles, psychological aspects, personality traits, technology use, and age also influenced students’ learning processes and outcomes. It can be shown from personal characteristics and experiences of the learner, social and cultural environment both inside (virtual/ offline meeting) and outside (online assignment/ project/ task-based) of the classroom, the opportunities for communication, access to both oral and written corrective feedback and instruction let by teachers. Those factors were not fully controlled by the teachers but understanding those aspects will make teachers able to consider how students learn English in effective ways to mitigate their learning loss in rapid knowledge growth and technological advancement era. This study reflected teachers’ development on their professionalism and their contribution to the second language acquisition theories. Keywords: Language acquisition and learning, Teacher Professional Development, Linguistics, and Non-linguistics Factors, covid19 pandemic